Uso del registro de solicitudes de medicamentos no incluidos en el listado de medicamentos esenciales como nueva fuente de información en los sistemas nacionales de farmacovigilancia (2013)
ABSTRACT: Objective: To describe the frequency of adverse drugs events (ADEs) as possible causes of request of drugs not included in national essential Medicines list in Colombia. Methods: This was a descriptive study developed in a private medical insurance company in Bogota, Colombia. Data were obtained from drug request form of drugs not included in a national essential Medicines list. We analyzed the content of the notes to identify the records related to the occurrence of ADEs in the period 2008 to 2009. Information concerning the adverse event and the drug involved was recorded in a data collection instrument developed by the researchers. The pharmacological classification of drugs was performed according to the Anatomical Therapeutic Chemical Classification System (ATC). Results: We study 3,336 request forms of drugs not included in a national essential Medicines list. The level 1 groups of the ATC of drugs with greater frequency of ADEs were the cardiovascular agents (47%), nervous system agents (24%) and antineoplastic and immunomodulating agents (15%). The great majority was cases of light severity (62.7%) and classified as possible (48.4%). Conclusion: The results of this study support the innovative approach of using request form of drug not included in national essential Medicines list to obtain information regarding ADEs in developing countries; recognizing the importance of looking for new sources of report of adverse reactions to diminish the under-notification of ADEs.